2018
DOI: 10.1089/scd.2018.0146
|View full text |Cite
|
Sign up to set email alerts
|

Label-Retaining, Putative Mesenchymal Stem Cells Contribute to Murine Myometrial Repair During Uterine Involution

Abstract: Uterine remodeling during pregnancy is a fundamental, dynamic process required for successful propagation of eutherian species. The uterus can increase in size up to 40-fold during pregnancy, which is largely attributed to expansion of the myometrium by hyperplasia and hypertrophy. After pregnancy, the uterus repairs the remodeled or ''damaged'' tissue during uterine involution (INV). Little is known about this repair process, particularly the role of mesenchymal stem/progenitor cells. The objective of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…In fact, both ATP and adenosine are involved in the immunomodulatory capacity and in the lineage commitment of the MSCs. Nucleotides have been associated with the proliferation [8,10,11,13,21,50] and differentiation of MSC's [16,17,48], while adenosine is involved in the survival of MSCs [8], proliferation (with an opposite ATP effect) [21], and lineage commitment [15,19,48]. Given the implications of nucleotides and nucleosides in the maintenance and behavior of MSCs, ectonucleotidases play a necessary role in the maintenance of the homeostasis of the perivascular stem cell niche.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, both ATP and adenosine are involved in the immunomodulatory capacity and in the lineage commitment of the MSCs. Nucleotides have been associated with the proliferation [8,10,11,13,21,50] and differentiation of MSC's [16,17,48], while adenosine is involved in the survival of MSCs [8], proliferation (with an opposite ATP effect) [21], and lineage commitment [15,19,48]. Given the implications of nucleotides and nucleosides in the maintenance and behavior of MSCs, ectonucleotidases play a necessary role in the maintenance of the homeostasis of the perivascular stem cell niche.…”
Section: Discussionmentioning
confidence: 99%
“…We also find NTPDase2 + SUSD2 + perivascular cells in human myometrium, pointing to the presence of an equivalent number of MSCs as found in the endometrium, which is consistent with the shared embryonic origin of the two tissues. In fact, Patterson et al identified PGFRβ + CD146 + perivascular, possibly progenitor, cells in murine myometrium [50] although functional studies need to be done. They found that this population of cells was label-retaining and not sensitive to female hormones, two features that indicate their possible role as progenitor cells in the myometrium.…”
Section: Discussionmentioning
confidence: 99%
“…These studies clearly illustrate how labeling under different physiological circumstances impacts which cells retain label. Recently, myometrial LRCs were characterized using the H2Bj-GFP transgenic labeling model (Patterson et al 2018). The brightest LRCs expressed the putative human stromal and myometrial MSC markers, CD140b and CD146, were perivascular, and preferentially proliferated during menses-like uterine involution.…”
Section: Label-retentionmentioning
confidence: 99%
“…The brightest LRCs expressed the putative human stromal and myometrial MSC markers, CD140b and CD146, were perivascular, and preferentially proliferated during menses-like uterine involution. Similar to putative human uterine stem cells, mouse uterine LRCs expressed little-to-no ESR1 and PGR (Chan & Gargett 2006b, Chan et al 2012, Wang et al 2012, Patterson et al 2018.…”
Section: Label-retentionmentioning
confidence: 99%
“…11 Interestingly, endometrial regeneration was found in the uterus of immunocompromised mice after the transplantation of human EMSCs, which suggested an important role for EMSCs in endometrial regeneration and repair. 12 Studies on EMSCs have mainly focused on clinical applications, while few studies have focused on the roles of EMSCs in endometrial repair in IUA patients to date. Therefore, we compared the biological characteristics and functions of EMSCs from patients with moderate-to-severe IUA caused by surgery with those from normal women to verify whether the occurrence of IUA is related to the loss or dysfunction of EMSCs.…”
Section: Introductionmentioning
confidence: 99%